Young FSU Migrants in Germany: Educational Attainment and Early Labor Market Outcomes - Regina Flake (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This study analyzes the educational attainment and early labor market outcomes of young migrants from the Former Soviet Union (FSU) who arrived in Germany between 1989 and 1994. The results reveal that migrants have lower educational attainments than natives, and that within the group of migrants, Jewish migrants perform better than ethnic German migrants. A decomposition analysis reveals that this competitive edge can, for the most part, be explained by a higher socioeconomic background. In the labor market, migrants cannot compensate for their educational disadvantage and have poorer labor market outcomes than natives. The results of this study stress the importance of an early educational integration of migrants for a successful labor market integration in the long run. – – Diese Studie analysiert den Bildungserfolg und die Arbeitsmarktintegration von jungen Migranten aus der ehemaligen Sowjetunion, die zwischen 1989 und 1994 nach Deutschland eingewandert sind. Die Ergebnisse zeigen, dass Migranten einen geringeren Bildungserfolg als Einheimische haben. Innerhalb der Gruppe der Migranten aus der ehemaligen Sowjetunion sind jüdische Migranten erfolgreicher als (Spät-)Aussiedler. Eine Dekompositionsanalyse zeigt, dass dieser Vorsprung größtenteils durch den soziökonomischen Hintergrund erklärt werden kann. Auf dem Arbeitsmarkt können Migranten ihren Bildungsnachteil nicht ausgleichen und haben größere Probleme bei der Arbeitsmarktintegration als Einheimische.
Keywords: F22; I20; J30; J60; J62; 330; international migration; education; wages; unemployment; intergenerational; mobility; integration